2022
DOI: 10.1101/2022.11.17.22282473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceptions and compliance with COVID-19 preventive measures in Southern and Central regions of Mozambique: a quantitative in-person household survey in the districts of Manhiça and Quelimane

Abstract: Background The COVID-19 pandemic has led countries into urgent implementation of stringent preventive measures at the population level. However, implementing these measures in low-income countries like Mozambique was incredibly difficult, coupled with lack of scientific evidence on the community understanding and compliance with these measures. This study assessed the perceptions and implementation of COVID-19 preventive measures recommended by Mozambican authorities in Manhiça and Quelimane districts, taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This study is part of a broader examination within the Child Health and Mortality Prevention Surveillance (CHAMPS) network to analyze the consequences of COVID-19 lockdowns for child health and mortality [14][15][16][17]. Leveraging the established platform of the CHAMPS Network of Health and Demographic Surveillance Systems (HDSSs) [18], we administered a short questionnaire to all households in a rural district [19]. Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) reporting guidelines for cross-sectional studies were followed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study is part of a broader examination within the Child Health and Mortality Prevention Surveillance (CHAMPS) network to analyze the consequences of COVID-19 lockdowns for child health and mortality [14][15][16][17]. Leveraging the established platform of the CHAMPS Network of Health and Demographic Surveillance Systems (HDSSs) [18], we administered a short questionnaire to all households in a rural district [19]. Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) reporting guidelines for cross-sectional studies were followed.…”
Section: Methodsmentioning
confidence: 99%
“…A survey instrument was developed to collect information about households' experiences during the COVID-19 lockdown, which included information on knowledge regarding COVID-19 symptoms, transmission, and prevention [22]. Questions were based on guidelines issued by the Ministry of Health for COVID-19 prevention in Mozambique [23].…”
Section: Data Collection and Quality Assurancementioning
confidence: 99%
See 2 more Smart Citations
“…The COVID-19 lockdown dataset analyzed for this study can be found in the CHAMPS Population Surveillance Dataverse [link]. [54] The Manhiça HDSS data that was used in combination with the COVID-19 lockdown dataset are available from the authors upon reasonable request.…”
Section: Declarationsmentioning
confidence: 99%